Simple Financial Bookkeeping Training for MSME Actors in Cikeusik Village - Meylani, Miftah; Hurriyaturrohman, Hurriyaturrohman (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are important for economic growth and development in Indonesia. The existence of MSMEs is also able to absorb labor and reduce unemployment. Not a few people in Cikeusik Village work as entrepreneurs, especially SME entrepreneurs such as food stalls. Many business actors have been in business for a long time but have not been able to develop well. This is due to the lack of understanding of business actors in financial bookkeeping. Community service carried out is to disseminate information to MSMEs in Cikeusik Village, namely about simple financial bookkeeping so that business actors can control business finances. Based on the explanation above, this community service aims to provide insight, and knowledge and make their own about simple financial bookkeeping, so that business actors can control expenses, income, and profits and can develop well in the future. This activity is carried out using interview, discussion, and practice methods. The results of the socialization activities showed a positive response from the community as seen from the enthusiasm of business actors to make simple financial bookkeeping properly.